Minimal processing of Durio zibethinus cultivar Puyat - Melodias, Cybelle Marie Canda (College of Home Economics, University of the Philippines Diliman, 2012)
The study adapted a minimal processing technology for frozen Durio zibetihinus cultivar Puyat puree. A more advanced maturity level of durian fruits from two test maturity levels was used for minimal processing and freezing because of its more intense yellowness and aroma, slightly lower pH level, and higher TSS concentration. The application of modified Food and Agriculture Organization of the United Nations Combined Preservation Technologies (FAO-CPT) for fruits and vegetables that included dehusking and deseeding, addition of 0.1% (wt/wt) potassium sorbate, 0.015% (wt/wt) sodium metabisulfite, pureeing, packing and sealing in 20cm x 30cm PE bags, improved the texture and appearance of the durian puree prior to blast freezing at -42 ± 20C for 8 h without significantly compromising the durian flavour. Five freeze-thaw cycles at -12 ± 20C for 72 h and 4 ± 20C for 12 h were applied to the durian purees and attributed to freezing injury observed through reduction of durian flavour, color fading, increased pH, decreased TSS, reduced viscosity, and inhibited microbial growth up to the third freeze-thaw cycle. Sorbate and sulfite treatments reduced flavour changes, prevented browning and malolactic fermentation, but also caused increased fluidity. The minimal processing technology for frozen durian cultivar Puyat puree adapted in the present study extended the overall acceptability of the product up to five freeze-thaw cycles. The modified FAO-CPT for fruits and vegetables with further enhancements, such as the use of a hydrocolloid to further stabilize the puree texture, the test Maturity 2 level durian cultivar Puyat fruits, and a maximum of five freeze-thaw cycles are recommended for developing a minimally processed frozen durian puree.